The Effect of the Addition of Fragrant Citronella Oil and Rhodinol to the handsanitizer on the Antibacterial Power of Staphylococcus aureus - Aji Hendra Sarosa; Vivi Nurhadianty; Luthfi Kurnia Dewi; Chandrawati Cahyani (Journal of Innovation and Applied Technology, 2022)
Hand sanitizer is an alternative to washing hands, it can also be antibacterial. Citronella and rhodinol oils consists of monoterpene compounds with major components in the form of aldehydes and alcohol. The oils have antibacterial properties. This study aims to increase the antibacterial power of the hand sanitizer by adding citronella and rhodinol. The experimental research method was carried out in a laboratory with two stages. The first stage was making hand sanitizers with variations in the addition of citronella and rhodinol. The second stage is to test the antibacterial power of the products. The addition of citronella oil and rhodinol can increase the inhibition zone against Staphylococcus aureus bacteria. The addition of rhodinol as an additive to the hand sanitizer gave a greater inhibition zone effect than the addition of citronella oil. The good result is a hand sanitizer made from 96% alcohol with 1% rhodinol additive.